Analogies at war : Munich, Vietnam, and the Bush administration decision-making during 1990-1 Gulf War. - Chen, Jeffrey Kwang Wai. (2008)
The reasons why the United States led a multinational coalition and intervened militarily to reverse the annexation of Kuwait by Iraq has been widely debated. This essay presents the systemic-cum-national interest and the psychological approach in examining the reasons for the intervention and the form that it took. While the systemic-cum-national interest approach is able to explain military intervention owing to various national interests in collusion with that of United States' national interest, the reasons why it took the form that it took remains unexplained. In contrast, the psychological approach is able to explain not only why military intervention took place (owing to the 1930s Munich analogy), the form that it took, was owing to the perceived failure of Vietnam. Thus, the objective and strategy of the 1990-1 Gulf War was taken from the two lessons of history that impacted on President Bush, as he made the decisions leading to militarily intervention. In conclusion, both the systemic-cum-national interest and psychological approaches were important; as the former was the precondition while the latter explained the form it took. In essence, both approaches need not be antithetical to one another, rather they were opposite sides of the same coin that lead to Bush's decision to wage war against Iraq to reverse the annexation of Kuwait.